Pemeliharaan Ayam Broiler Kandang Closed House dengan Sistem Koloni - Marenda Julian Wibowo; Erna Indriastiningsih; Anita Oktaviana Trisna Devi (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Entrepreneurs are the main actors in economic development with their function as innovators or creators of new creations. Entrepreneurship has many types and fields, one of which is broiler farming. Broiler farming can be done using cages with open house and closed house types. Broiler farming has a relatively short maintenance time, there are three maintenance phases, namely the pre-stater phase, stater phase, and finisher phase. In order to produce quality chickens, farmers must know how to raise broilers properly and recognize the various diseases that can infect broilers. Broiler farming with a partnership system is very helpful for farmers in terms of facilities and infrastructure for raising chickens and selling chickens. Closed house chicken cages with a colony system have the advantage of being able to maximize the number of chicken populations with limited land conditions, cleaner cages, faster chicken growth and are in accordance with standards for raising broiler chickens. However, colony type cages have disadvantages compared to postal type closed housed cages which are cheaper to build, and have lower operational costs.